HUBUNGAN SIKAP DENGAN PERILAKU PENGELOLAAN SAMPAH RUMAH TANGGA DI DESA POTO - Desy Fadilah Adina Putri; Putri Adekayanti; Evi Rosmiana; Nadia R. Kaleka (Journal of Innovation Research and Knowledge, 2025)
Poto Village has a Community Development Program (P2PM) focused on tree planting and waste management. Given the village's numerous awards, researchers wanted to understand attitudes and behaviors regarding household waste management, particularly in supporting the program. The research design used was quantitative with a descriptive approach.cross section. The number of research samples was 30 respondents and used total sampling technique. Data analysis technique used fisher exact statistical test. The results of the study showed that positive attitudes had behavior of not managing household waste as many as 17 people (58.6%) greater than those who had behavior of managing waste obtained sig 1.000>α=(0.05), meaning Ho is accepted and Ha is rejected. It can be concluded that there is no relationship between attitudes and behavior of household waste management in Poto Village, Sumbawa Regency. A good attitude towards waste management does not always ensure that someone will actually implement proper waste management behavior